Model Effectiveness Good Lavoie The acquisition of biological concepts for secondgrade intermediate students - Majeed Aziz, Iman (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to identify the effectiveness of a model good lavoie In acquiring the scientific concepts of the second grade students, the average of the biology, to achieve the goal of the research, the following null hypothesis was formulated: There is no statistically significant difference at the level of significance 0.05 Demonstrate the average degree of acquisition of the scientific concepts that they have studied according to a model good lavoie With a biology subject and the average degree of acquisition of the control group’s students of the scientific concepts they studied According to the usual method,The research sample consisted of 60 students, and they were distributed in two groups A, B By 30 For the experimental group, A Indeed, 30 students for the control group B The covent groups in the IQ test variables test the previous information in material biology To collect data to verify the aim of the research, a search tool has been prepared to measure the acquisition of scientific concepts Sister b acquired scientific concepts and the results of the search outweigh the students of the experimental group that studied According to the model, good lavoie On the students of the control group, who studied according to the usual method